1995
DOI: 10.2355/isijinternational.35.982
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Behavior and Microstructures in Ultra-low Carbon Steels.

Abstract: Fe-0.002010C. Fe-0.01010C. Fe-1 .50/0Mn-0.0010/0C and Fe-1 .50/0Mn-0.010/oC steels were vacuum-melted and examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…1,2) In addition, the terminology of the microstructures 2,3) is confusing. Shibata and Asakura 4) observed g→a transformation in an ultralow-carbon steel in detail and found that the grain diameter of a did not decrease much even when the cooling rate was increased. Together with polygonal ferrite (a p ), 3,5) of which the grain boundaries are planar, and quasi-polygonal ferrite (a q ), 3,5) of which grain boundaries are curved or ragged, a variety of intermediate microstructures and martensite were observed and were found to be dependent of the cooling rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2) In addition, the terminology of the microstructures 2,3) is confusing. Shibata and Asakura 4) observed g→a transformation in an ultralow-carbon steel in detail and found that the grain diameter of a did not decrease much even when the cooling rate was increased. Together with polygonal ferrite (a p ), 3,5) of which the grain boundaries are planar, and quasi-polygonal ferrite (a q ), 3,5) of which grain boundaries are curved or ragged, a variety of intermediate microstructures and martensite were observed and were found to be dependent of the cooling rate.…”
Section: Introductionmentioning
confidence: 99%
“…Together with polygonal ferrite (a p ), 3,5) of which the grain boundaries are planar, and quasi-polygonal ferrite (a q ), 3,5) of which grain boundaries are curved or ragged, a variety of intermediate microstructures and martensite were observed and were found to be dependent of the cooling rate. In order to examine the relationship between the g grain boundary and the a grain of an ultralowcarbon steel, the present authors 4,6,7) performed several experiments. For instance, they thermally etched g grain boundaries and attempted to observe the grain boundaries of both g and a grains simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…However slower cooling rate during continuous cooling of the TMCP steel leads to the formation of what has been termed granular bainite by Krauss et al 13) The grain boundary phase in Fig. 4 is precluded from being considered acicular ferrite (due to Shibata et al 12) ) or the bainitic ferrite on ground that while the former nucleates intragranularly, the latter, when formed at the grain boundaries is generously associated with MA constituents. Even rectangular bainite due to Tian et al 5) reportedly contains a high amount of non-aligned second phase particles.…”
Section: Microstructuresmentioning
confidence: 99%
“…It is in general, difficult to differentiate between martensite and bainite in this low carbon HSLA steels but previous workers have used the lath width as the yardstick of describing martensite or bainite. 12) Following that, the laths in Fig. 5 are said to be of martensites.…”
Section: Microstructuresmentioning
confidence: 99%
“…As the cost of tempering after reheating and quenching is high, so using tempering after TMCP process to instead it is of great significance. During this new process, through reasonable design of rolling and cooling, the high density dislocation that formed during the low temperature severe finishing rolling can be reserved, then the nuclear point during the phase deformation will be increased, the microstructures is refined, after tempering, the comprehensive mechanical properties of the steel will be finally improved [3]. In this paper, niobium and titanium microalloying steel was chosen as the study object, by tempering after TMCP process, bainite steel with higher yield strength was finally prepared, the effect of tempering temperature on microstructures and mechanical properties of this steel was investigated.…”
Section: Introductionmentioning
confidence: 99%